Original Database for "Why and How European Farmers Are Dedicated to Breeding the Dwarf Dahomey Cattle" - Vanvanhossou, Sèyi; Justus Liebig University Giessen (My University, 2021)
The current raw data supports the findings in the research paper "Why and How European Farmers Are Dedicated to Breeding the Dwarf Dahomey Cattle". It was generated from a survey of the breeding systems of the Dahomey cattle in European countries. An open-closed questionnaire were prepared on the “Google Form” online platform and submitted to the members of the Verband Europäisches Dahomey-Zwergrind and the “Verein Dahomey Schweiz” between Mai and October 2021.
Keywords: African shorthorn taurine; small-sized cattle; landscape values; breeding systems; resistance to diseases